Low temperature and controlled synthesis of Bi2(S1−xSex)3 thin films using a simple chemical route: effect of bath composition. Issue 70 (31st July 2015) - Salunkhe, Manauti M.; Khot, Kishorkumar V.; Sahare, Sanjay H.; Bhosale, Popatrao N.; Bhave, Tejashree
<x xml:space="preserve">Abstract</x> Nanostructured Bi2(S1−xSex)3 thin films were synthesized using a simple chemical bath deposition method at room temperature, and their photoelectrochemical performance was tested.